INTEGRITY IN LAW ENFORCEMENT POLICE ETHICS AND RESPONSIBILITIES - Ahmad Azhari; Fika Novatiana; Insan Kamil Sinaga; Mahmuddin Adriansyah (PT. Jurnal Center Indonesia Publisher, 2025)
Service good society and enforcement​ law is very important For guard state order and security . Research This investigate How ethics and integrity police relate with analyze draft ethics and integrity police . The purpose of study This is For understand role the important role played by moral values and integrity in operation Police . Research This aiming For explain How ethics and honesty can entered to in practice police For increase quality service public and strengthen connection between police and society . Research This use methodology qualitative For do it . Enforcement law and services good society​ play role important in guard state order and security . Research This aiming For investigate connection between ethics and integrity member police . With analyze draft ethics and integrity member Police . Research This aiming For understand role the key played by moral values and integrity in police . Through approach qualitative For analyze , research This try to describe How ethics and integrity can integrated in a way pragmatic in practice policing For increase quality service public and strengthen connection between police and society .